Activation of ZrO2–WO3 solid acid catalysts in a Friedel–Crafts reaction through post-hydrothermal treatment. Issue 21 (4th May 2022) - Li, Sha; Yu, Ruopeng; Xu, Bonan; Wang, Zhikun; Wu, Chunzheng; Guo, Jianzhong
Abstract : The high pH value of the post-hydrothermal treatment induces the generation of acidic WO x cluster active sites. Abstract : ZrO2 –WO3 mixed oxide plays an essential role in the chemical and petroleum industries. So far, very little work has paid attention to the activation of the low activity of ZrO2 –WO3 catalysts. In this work, poorly reactive ZrO2 –WO3 was prepared as a model catalyst by a sol–gel method and it was accompanied by post-hydrothermal treatment with various solutions. The catalytic results in the Friedel–Crafts reaction of anisole and benzyl alcohol showed that the post-hydrothermal treatment with ethylenediamine or ammonium hydroxide solutions dramatically improved the activity of ZrO2 –WO3, while the hydrothermal treatments with water or ammonia chloride solution resulted in poorer activity and selectivity. The former treatments were found to induce a huge transformation of the ZrO2 crystal from monoclinic to tetragonal as well as a significant increase in acidic WO x clusters that anchored onto ZrO2 . The generation of the WO x clusters was responsible for the activation of ZrO2 –WO3 .